Techno-economic and life cycle assessment of a nanofluid-based concentrated Photovoltaic/Thermal-Thermoelectric hybrid system - Lekbir, Abdelhak (Elsevier B.V., 2024)
The Photovoltaic/Thermal-Thermoelectric hybrid system (PV/T-TEG) effectively improves the solar energy conversion rate. This work presents the environmental, exergy, and economic performance of a nanofluid-based concentrated PV/T-TEG hybrid system. The analysis has considered two types of TEG material with different characteristics. An in-house MATLAB code has been developed to model the hybrid system and evaluate its performance. In addition, a comparative study is carried out to contrast the proposed hybrid system's performance against conventional configurations, namely: standard concentrator PV module (SCPV), nanofluid-based concentrated PV/Thermal system (NCPV/T), and a heat sink-based concentrated PV/thermoelectric system (HSCPV/TEG). The simulation output reveals that at the optimum value of solar concentration C=5, and operating temperature of 35°C, the average exergy efficiency of the proposed NCPV/T-TEGA is about 15.28 higher by 2.37, 3.13, 5.83, 7.32, and 7.43 compared to NCPV/T-TEGB, NCPV/T, HSCPV/TEGA, HSCPV/TEGB, SCPV, respectively. According to environmental analysis, it has been found that the NCPV/T-TEGA configuration engendered the highest CO2 emissions during the manufacturing phase. However, during the production phase (over 25 years), a 1m2 of NCPV/T-TEGA hybrid system provided the highest GWP avoidance of 1208.9kg.CO2.eq.m−2.year−1. © 2024 Elsevier B.V.